On the numerical solution of two point boundary value problem for the Helmholtz type equation by finite difference method with non regular step length between nodes - Pramod Pandey (Qubahan Academic Journal)
In this article, we have presented a variable step finite difference method for solving second order boundary value problems in ordinary differential equations. We have discussed the convergence and established that proposed has at least cubic order of accuracy. The proposed method tested on several model problems for the numerical solution. The numerical results obtained for these model problems with known / constructed exact solution confirm the theoretical conclusions of the proposed method. The computational results obtained for these model problems suggest that method is efficient and accurate.